Shift work and sleep pattern disturbances of nurses at bua health center : a correlation study - Nurhaenih, Nurhaenih; Pratiwi, Santi; Sugiyanto, Sugiyanto; Hoesny, Rezkiyah (Jurnal Konseling dan Pendidikan, 2025)
Shift work is an essential aspect of healthcare services, particularly in facilities such as the BUA Health Center. However, it has been widely documented that shift work can disrupt sleep patterns, leading to significant health issues for workers, including nurses. This study aims to examine the relationship between shift work and sleep pattern disturbances among nurses at the BUA Health Center. Utilizing a qualitative approach and a literature study methodology, this research explores existing academic literature, case studies, and surveys from healthcare workers to understand the extent of sleep disturbances among nurses working various shifts. The analysis identifies that irregular sleep patterns, sleep deprivation, and poor quality of sleep are prevalent among nurses working rotating or night shifts. These disturbances have been shown to negatively affect both physical health and mental well-being, contributing to increased fatigue, decreased cognitive function, and a higher risk of burnout. Furthermore, the literature suggests that shift work impacts job performance and overall work satisfaction. This study underscores the need for effective strategies to mitigate the negative effects of shift work, including improved scheduling, better sleep hygiene practices, and organizational interventions. Recommendations include more flexible work schedules and the incorporation of regular sleep assessments to monitor the health of nurses. This research calls for further studies to develop interventions and policies that address the specific needs of healthcare professionals in shift-based roles.